2021
DOI: 10.1021/acs.jafc.1c04774
|View full text |Cite
|
Sign up to set email alerts
|

Round Scad-Derived Octapeptide WCPFSRSF Confers Neuroprotection by Regulating Akt/Nrf2/NFκB Signaling

Abstract: We previously identified peptides derived from round scad as potential Nrf2 activators. However, the neuroprotection of these peptides is still unclear. In this study, we aimed to investigate the neuroprotective effect of WCPFSRSF against glutamateinduced neurotoxicity, and the memory-improving effects of WCPFSRSF in mice were also explored. Results showed that WCPFSRSF ameliorated oxidative stress by improving the activities of antioxidant enzymes and promoting the Nrf2-mediated endogenous defense system. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…Our previous transcriptome study suggested that WCPFSRSF altered the inflammatory-related pathways including TNF, NFκB, IL-17, and IL-6 pathways in the hippocampus of mice . WCPFSRSF also acted as a Keap1 inhibitor to modulate the Nrf2-related endogenous antioxidant system in cells . Therefore, Keap1 protein and other 10 inflammatory-related biomacromolecules were selected.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous transcriptome study suggested that WCPFSRSF altered the inflammatory-related pathways including TNF, NFκB, IL-17, and IL-6 pathways in the hippocampus of mice . WCPFSRSF also acted as a Keap1 inhibitor to modulate the Nrf2-related endogenous antioxidant system in cells . Therefore, Keap1 protein and other 10 inflammatory-related biomacromolecules were selected.…”
Section: Resultsmentioning
confidence: 99%
“…Lactate dehydrogenase (LDH) and reactive oxygen species (ROS) were measured as previously described . Briefly, the cells were seeded at a density of 2 × 10 5 cells/mL on 96-well plates for 24 h; then, peptides dissolved in the medium were added to the culture for 24 h in the presence of glutamate, and the levels of LDH and ROS were measured by analysis kits (Beyotime Biotechnology Institute).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to its relatively small size, dark colour, susceptibility to spoilage, and poor taste, it is not suitable for commercial fish consumption [ 66 ]. In this regard, the biological antioxidant capacity and mechanism of Round scad protein-derived peptides WCPFSRSF and ILGATIDNSK have been confirmed [ 43 , 67 ]. Thus, a broad range of marine organisms or by-products can be exploited as raw materials for the elaboration of natural antioxidants, meaning that it has the potential to be used as a functional ingredient in the food, cosmetic, and pharmaceutical industries.…”
Section: Sources Of Antioxidant Peptidesmentioning
confidence: 99%